2020
DOI: 10.3390/w12020468
|View full text |Cite
|
Sign up to set email alerts
|

Improved Planning of Energy Recovery in Water Systems Using a New Analytic Approach to PAT Performance Curves

Abstract: The use of pumps working as turbines (PATs) to improve the energy efficiency of water networks has been studied in the last years. This recovery system is justified due to a low investment contrasting with the capacity to take advantage in certain points with low and medium recoverable heads. Analyses of water systems using simulation software and/or optimization algorithms need the characteristic curves (head and efficiency) of the machines, which should be known with minor error by the water managers. The kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 25 publications
0
36
0
3
Order By: Relevance
“…The estimation of the behavior of pumps in their turbine mode has been an important issue and has led to numerous studies. Unfortunately, most of the studies did not have enough pumps for experimentation and therefore their results lack a certain precision [20] The characteristics curves of a machine can be defined by polynomial equations depending on the specific speed (n s ) of the machine. When there is only a suction pipe, this value is used to classify either pumps (n SP ) or pumps in turbine mode (n ST ).…”
Section: B-2 Selection Of a Standard Water Pump By Catalog Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The estimation of the behavior of pumps in their turbine mode has been an important issue and has led to numerous studies. Unfortunately, most of the studies did not have enough pumps for experimentation and therefore their results lack a certain precision [20] The characteristics curves of a machine can be defined by polynomial equations depending on the specific speed (n s ) of the machine. When there is only a suction pipe, this value is used to classify either pumps (n SP ) or pumps in turbine mode (n ST ).…”
Section: B-2 Selection Of a Standard Water Pump By Catalog Datamentioning
confidence: 99%
“…When there is only a suction pipe, this value is used to classify either pumps (n SP ) or pumps in turbine mode (n ST ). These values are determined by the following expressions [20]:…”
Section: B-2 Selection Of a Standard Water Pump By Catalog Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Their analysis indicated that a really attractive capital payback period could be achieved if PATs are installed in the pipes located close the water supply node. Pérez-Sánchez et al [34] defined a new approach to estimating the PAT best efficiency point and predicting its energy performance curve, the accuracy of which was verified using an experimental database. However, due to the fixed geometrical characteristics and inner flow space, the PAT performance in terms of head reduction was easily affected by the variation of flow discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Paper [12] studied the use of pumps working as turbines (PATs) to improve the energy efficiency of water networks. Analyses of water systems using simulation software and/or optimization algorithms require accurate characteristic curves (head and efficiency) of the machines.…”
mentioning
confidence: 99%